Plasma biopsy by Tag-sequencing: an acceptable alternative to tumor tissue profiling in non-small-cell lung cancer - Mehta, Anurag; Kumar Sharma, Sanjeev; Kumar, Dushyant; Vasudevan, Smreti (Polish Journal of Pathology, 2021)
Tag-sequencing is a modified next-generation sequencing (NGS) approach wherein targeted regions are tagged with unique molecular identifiers enabling error-free detection of rare genomic alterations. We aimed to perform this high- fidelity sequencing to identify actionable variants from the plasma of lung cancer patients. Targeted sequencing was performed from plasma-derived cell-free nucleic acid in twenty-one advanced, treatment naïve, non-small-cell lung cancer (NSCLC) patients. Clinically significant genetic alterations were compared with matched tumor NGS profile for each patient (patient-level), and separately for each alteration (variant-level). Cross-platform validation was done for EGFR and KRAS mutations (real-time PCR) and ALK1 rearrangement (immunohistochemistry). Forty-seven alterations (26 in plasma and 21 in tumor tissue) were detected in 19/21 tested cases. Overall-concordance between the two assays was 94.87% (κ of 0.71, 95% CI: 0.54-0.89). Patient-level and genic-concordance was 57.1% (12/21 cases) and 67.86%, respectively. Almost perfect agreement was reached for detecting actionable EGFR mutations and ALK1 rearrangement (κ of 0.89 and κ of 1, respectively), which was confirmed by single-gene testing. Substantial agreement between the assays makes Tag-sequencing a viable option for identifying multibiomarkers from the plasma of advanced NSCLC patients in special circumstances where tissue has depleted/tumor is inaccessible/high risk of biopsy due to existing comorbidities.